An isocitrate lyase gene-deleted strain of Nocardia seriolae in live attenuated vaccine development against fish nocardiosis - Lin, Guanying; Li, Yan; Hou, Suying; Wen, Yiming; Lei, Xiaoya; Huang, Ting; Chen, Yuben; Chen, Jianlin; Xia, Liqun (Frontiers in Veterinary Science, 2025)
BackgroundFish nocardiosis caused by Nocardia seriolae is a severe bacterial disease in aquaculture, causing significant economic losses. The effectiveness of antibiotics in dealing with nocardiosis induced by N. seriolae is not satisfactory. NsICL is a potential virulence factor in N. seriolae based on its crucial role in the glyoxylate cycle, its identity as a secreted protein, and its established role in virulence and intracellular survival in homologous pathogens such as Mycobacterium tuberculosis. so, the NS-ΔICL deletion strain was constructed to investigate its function.MethodsThe NsICL gene was knocked out via homologous recombination to generate the mutant strain NS-ΔICL. Comparative analysis of morphology, growth, and virulence was performed between the mutant and wild-type strains. The NS-ΔICL strain was used to immunize hybrid snakehead (Channa maculata♀ × Channa argus♂), with immune responses evaluated through non-specific immune parameters, specific antibodies, and expression levels of immune-related genes. Protective efficacy was assessed by challenge tests.ResultsNS-ΔICL showed reduced virulence (LD50 = 2.60 × 105 cfu/fish) compared to the wild-type strain (LD50 = 4.32 × 104 cfu/fish). Immunized fish exhibited significantly higher levels of non-specific immune factors (AKP, ACP, POD, LZM) and specific IgM antibodies. Immune-related genes (MHCIα, CD4, IL-8) were upregulated in vaccinated fish. Relative percentage survival (RPS) was 77.03% in vaccinated fish after challenge tests, which indicating strong protective efficacy.ConclusionThe NS-ΔICL deletion strain was successfully constructed in this study. It can not only induce humoral and cellular immunity in fish but also effectively protect fish against N. seriolae infection. These results provide a foundation for the development of a live attenuated vaccine for treating fish nocardiosis.